KEMISKINAN RUMAH TANGGA SEKTOR INFORMAL DI ACEH - Nuri Rosmika (JURNAL EKOMBIS, 2021)
Aceh Province as the poorest province on the island of Sumatra with business fields dominated by the informal sector. Especially in the midst of the Covid-19 pandemic which is very detrimental to these informal sector workers. Therefore, this study aims to see the determinants of poverty in informal sector worker households in Aceh Province through their socio-economic variables. The data source used was the 2019 National Socio-Economic Survey (SUSENAS) carried out by the Aceh Province Central Statistics Agency (BPS). Through logistic regression, it is known that poverty in the informal sector is more focused on households where the head of the household is under 50 years old, lives in rural areas, has 4 or more dependents, works below normal working hours, does not have access to finance and information technology. and communication. However, the variables of marital status, education, and sex of the head of household in the informal sector did not significantly influence the level of welfare. This is interesting to be investigated further.Provinsi Aceh sebagai Provinsi termiskin di Pulau Sumatera dengan lapangan usaha didominasi sektor informal. Apalagi di tengah pandemi covid-19 yang sangat merugikan pekerja sektor informal tersebut. Oleh karena itu, penelitian ini bertujuan untuk melihat determinan kemiskinan pada rumah tangga pekerja sektor informal di Provinsi Aceh melalui variabel sosial ekonominya. Sumber data yang digunakan adalah Survei Sosial Ekonomi Nasional (SUSENAS) tahun 2019 yang dilaksanakan oleh Badan Pusat Statistik (BPS) Provinsi Aceh. Melalui regresi logistik diketahui bahwa kemiskinan sektor informal  lebih berpusat pada rumahtangga dengan kepala rumah tangga berusia di bawah 50 tahun, tinggal di daerah pedesaan, memiliki jumlah tanggungan 4 orang atau lebih, bekerja di bawah jam kerja normal, tidak mempunyai akses terhadap keuangan serta teknologi informasi dan komunikasi. Akan tetapi variabel status perkawinan, pendidikan, dan jenis kelamin kepala rumahtangga sektor informal tidak berpengaruh secara signifikan terhadap tingkat kesejahteraannya. Hal ini menarik untuk diteliti lebih lanjut.